Visualizing lipid structure and raft domains in living cells with two-photon microscopy - Gaus, Katharina (National Academy of Sciences, 2003)
The lateral organization of cellular membranes is formed by the clustering of specific lipids, such as cholesterol and sphingolipids, into highly condensed domains (termed lipid rafts). Hence such domains are distinct from the remaining membrane by their lipid structure (liquid-ordered vs. -disordered domains). Here, we directly visualize membrane lipid structure of living cells by using two-photon microscopy. In macrophages, liquid-ordered domains are particularly enriched on membrane protrusions (filopodia), adhesion points and cell–cell contacts and cover 10–15% of the cell surface at 37°C. By deconvoluting the images, we demonstrate the existence of phase separation in vivo. We compare the properties of microscopically visible domains (<1 μm(2)), with those of isolated detergent-resistant membranes and provide evidence that membrane coverage by lipid rafts and their fluidity are principally governed by cholesterol content, thereby providing strong support for the lipid raft hypothesis.